2000
DOI: 10.2118/63009-pa
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Model and Numerical Investigation of Near-Wellbore Effects in Hydraulic Fracturing

Abstract: Summary The high near-wellbore pressure drop, which has frequently been reported in fracture treatments, is indicative of ineffective communication between the wellbore and the fracture. Although numerous observations of such effects have been published, few attempts have been made to understand them. This article describes three possible mechanisms of near-wellbore effects [perforation phasing misalignment-induced rock pinching, perforation pressure drop, and fracture reorientation (deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…Smooth reorientation was most commonly observed as fractures transitioned from longitudinal with the wellbore in the near-well zone to be perpendicular to the minimum principal stress further from the well. This curvilinear geometry was less apparent in our experiments than in previous works that used larger wellbores and more homogeneous materials (Abass et al 1996;Hallam and Last 1991;Romero et al 1995;Weijers et al 1994). Our most prominent examples of smooth reorientation were observed in E01-00-true-triaxially confined high-strength cement with brine injection and G01-90-true-triaxially confined granite with oil injection.…”
Section: Recurring Fracture Patterns At the Specimen Scalecontrasting
confidence: 72%
See 1 more Smart Citation
“…Smooth reorientation was most commonly observed as fractures transitioned from longitudinal with the wellbore in the near-well zone to be perpendicular to the minimum principal stress further from the well. This curvilinear geometry was less apparent in our experiments than in previous works that used larger wellbores and more homogeneous materials (Abass et al 1996;Hallam and Last 1991;Romero et al 1995;Weijers et al 1994). Our most prominent examples of smooth reorientation were observed in E01-00-true-triaxially confined high-strength cement with brine injection and G01-90-true-triaxially confined granite with oil injection.…”
Section: Recurring Fracture Patterns At the Specimen Scalecontrasting
confidence: 72%
“…Rock stresses are the dominant factor affecting fracture geometry with tensile hydraulic fractures preferentially orienting perpendicular to the minimum principal stress direction (Warpinski et al 1982a, b;Zoback et al 1977). The influence of the near-wellbore zone can add complexity to the fracture, where examples show that fractures tend to initiate with orientations parallel with the borehole axis even if the borehole is drilled parallel with the minimum principal stress (Hallam and Last 1991;Romero et al 1995). It is relevant to note that these studies observed an offset branching pattern along the wellbore when hydraulic fractures initiated at an angle other than perpendicular to the minimum principal stress (Weijers et al 1994), which is unlike the idealized curving pattern predicted by continuum theory (Abass et al 1996;Valkó and Economides 1995).…”
Section: Background: Hydraulic Fracture Geometrymentioning
confidence: 99%
“…If these perforations are not perpendicular to the minimum in‐situ stress, the fractures will reorient themselves toward the direction of least resistance. This can lead to highly non‐planar fracture surfaces near the wellbore, which may cause failure of hydraulic fracturing treatments . This problem is investigated in Section 7.3 with the proposed generalized FEM (GFEM).…”
Section: Introductionmentioning
confidence: 99%
“…If these perforations are not perpendicular to the minimum in-situ stress, the fractures will reorient themselves toward the direction of least resistance. This can lead to highly non-planar fracture surfaces near the wellbore, which may cause failure of hydraulic fracturing treatments [2]. This problem is investigated in Section 7.3 with the proposed generalized FEM (GFEM).Adachi et al [3] presented an exhaustive summary of early 2D models and the so-called Pseudo-3D (P3D) models currently used for hydraulic fracturing simulations in the industry.…”
mentioning
confidence: 99%
“…ey can be classified into the following four categories: (1) two-dimensional (2D) models (e.g., PKN model [11], KGD model [12], and penny-shaped model [13]), (2) pseudo three-dimensional (P3D) models (e.g., cell-based model [14] and lumped parameter model [15]), and (3) three-dimensional (3D) planar models [16]. However, these theoretical models are not widely used in applications as they are incapable of reproducing the 3D nature of hydraulic fractures and do not account for the near-wellbore effects and the interaction between natural and hydraulic fractures [17,18].…”
Section: Introductionmentioning
confidence: 99%